PENGARUH BRAND AMBASSADOR DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN PRODUK SCARLETT WHITENING PADA MAHASISWA ADMINISTRASI BISNIS UNIVERSITAS MALIKUSSALEH - Nayami Syarifuddin; Maisyura Maisyura (Program Studi Administrasi Bisnis, 2022)
This study aims to determine the influence of brand ambassadors and brand image on the purchasing decision of Scarlett Whitening products on Malikussaleh University Business Administration students. This research was conducted at the Business Administration Study Program of Malikussaleh Lhokseumawe University. This study used primary data in the form of questionnaires that were distributed to students of the Business Administration Study Program at Malikussaleh University as many as 67 respondents. The data analysis methods used are instrument tests and classical assumption tests as well as multiple linear regression tests using the help of SPSS software version 26. The test results showed that the brand ambassador variable did not have a significant effect on scarlett Whitening's product purchase decisions in Malikussaleh University Business Administration students, while the brand image variable had a positive and significant effect on Scarlett Whitening's product purchase decisions in Malikussaleh University Business Administration students. Meanwhile, the simultaneous test results showed that the brand ambassador and brand image together influenced the purchasing decision of Scarlett Whitening products in Malikussaleh University Business Administration students.